2020
DOI: 10.1088/1757-899x/963/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Types of heat exchangers in industry, their advantages and disadvantages, and the study of their parameters

Abstract: Annotation The heat exchanger as the main element in various types of energy complex is widely studied in technological and production processes. Heat exchangers are classified according to their application. Therefore, in this article we will consider the main types of heat exchange equipment, the choice of a specific type, depending on temperature, flow, pressure drop, and so on. The paper also provides a brief description of software for calculating, modeling and designing CFD, the advantages of each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The result of the first case of one tube and one pass heat exchanger as followings figures (9)(10)(11)(12)(13)(14). It is observed that in the temperature chart the temperature has lowest value in the inlet of the x direction nearly fixed and the then reached its maximum value after the mid of the heat exchanger.…”
Section: A Cfd Results For the First Casementioning
confidence: 94%
See 1 more Smart Citation
“…The result of the first case of one tube and one pass heat exchanger as followings figures (9)(10)(11)(12)(13)(14). It is observed that in the temperature chart the temperature has lowest value in the inlet of the x direction nearly fixed and the then reached its maximum value after the mid of the heat exchanger.…”
Section: A Cfd Results For the First Casementioning
confidence: 94%
“…If any constraints are imposed, iteration of one or more steps till all the requirements are met within the tolerable limits as a reconsideration of the conclusion must be taken into account. A particular design methodology has to be developed within the framework of these activities [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heat exchangers (HXs) are indispensable devices used to exchange thermal energy in the form of heat transfer/dissipation between fluids (liquid or gas), from one medium to another [1,2]. Pipes are one of the most heavily stressed major components of HXs used in harsh working environments, such as power plant sectors, resulting in frequent premature failures.…”
Section: Introductionmentioning
confidence: 99%
“…The heat exchanger is a thermal medium that transfers heat between two or more fluids at different temperatures [1][2][3]. Heat exchangers are widely utilized in industrial applications such as chemical processing systems, waste heat recovery units, power plants, food processing systems, air conditioning systems, refrigeration, heating, and automobile radiators [2].…”
Section: Introductionmentioning
confidence: 99%